2019
DOI: 10.1002/ana.25586
|View full text |Cite
|
Sign up to set email alerts
|

GGC Repeat Expansion of NOTCH2NLC in Adult Patients with Leukoencephalopathy

Abstract: Leukoencephalopathies comprise a broad spectrum of disorders, but the genetic background of adult leukoencephalopathies has rarely been assessed. In this study, we analyzed 101 Japanese patients with genetically unresolved adult leukoencephalopathy using whole‐exome sequencing and repeat‐primed polymerase chain reaction for detecting GGC expansion in NOTCH2NLC. NOTCH2NLC was recently identified as the cause of neuronal intranuclear inclusion disease. We found 12 patients with GGC expansion in NOTCH2NLC as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 11 publications
3
100
0
Order By: Relevance
“…Our study also demonstrates that inclusion criteria based on the characteristic MRI features of NIID strongly predicts the presence of NOTCH2NLC GGC repeat expansions. This compares favorably to the weak correlation of other clinical features with NOTCH2NLC GGC repeat expansion; Jiao et al and Okubo et al demonstrated NOTCH2NLC GGC repeat expansions in 0.4% and 11.9% of patients with patients with neurodegenerative dementia and leukoencephalopathy, respectively 23,24 …”
Section: Discussionmentioning
confidence: 79%
“…Our study also demonstrates that inclusion criteria based on the characteristic MRI features of NIID strongly predicts the presence of NOTCH2NLC GGC repeat expansions. This compares favorably to the weak correlation of other clinical features with NOTCH2NLC GGC repeat expansion; Jiao et al and Okubo et al demonstrated NOTCH2NLC GGC repeat expansions in 0.4% and 11.9% of patients with patients with neurodegenerative dementia and leukoencephalopathy, respectively 23,24 …”
Section: Discussionmentioning
confidence: 79%
“…Recent studies revealed a broadened clinical spectrum of adult‐onset NIID. GGC repeat expansion was not only identified in typical adult‐ or juvenile‐onset NIID patients 4 but also observed in Alzheimer disease (AD), 3 Parkinson disease (PD), 3 adult leukoencephalopathy, 25 and essential tremor (ET), 26 implicating that GGC repeat expansions in the NOTCH2NLC gene could partly contribute to the pathological process of multiple neurodegenerative diseases, including MSA, AD, PD, ET, and leukoencephalopathy. Therefore, we also agree to define a term NIID‐related disorders (NIIDRD), 3 which include NIID and other related neurodegenerative diseases caused by the GGC repeat expansion, although it might be a misdiagnosis in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Satoko Miyatake, MD, PhD, 2 Noriko Miyake, MD, PhD, 2 Jun Sone, MD, PhD, 3,4 Gen Sobue, MD, PhD , 4,5,6 Hideyuki Takeuchi, MD, PhD, 1 Naomichi Matsumoto, MD, PhD, 2 and Fumiaki Tanaka, MD, PhD 1 We appreciate the interest shown by Dr Yau and colleagues in our recent publication. 1 We read their letter with great interest, which explains that neuronal intranuclear inclusion disease (NIID) is rare in European leukoencephalopathy, in striking contrast to our results in Japanese leukoencephalopathy.…”
Section: Author Contributionsmentioning
confidence: 95%
“…We read with interest that Okubo et al identified GGC repeat expansion in NOTCH2NLC as the most frequent genetic cause of adult onset leukoencephalopathy in Japan. 1 After the initial discovery of the causative mutation for neuronal intranuclear inclusion disease (NIID), 2,3 all additional reported NIID patients with this mutation are East Asians. Adult onset genetic leukodystrophy is clinically and radiologically heterogeneous, making definitive diagnosis challenging.…”
mentioning
confidence: 99%